2017
DOI: 10.15406/mojap.2017.04.00133
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a Neural Stem/Progenitor Cell Marker Nestin in Salivary Glands

Abstract: Salivary glands have the ability to regenerate, yet the origin and markers of stem/progenitor cells involved in this regeneration are still unclear. We have previously reported that the expression of cytokeratin 5, which is considered as a marker of both basal/myoepithelial and progenitor cells in salivary glands, was enhanced by tissue injury. In this study, to identify more specific markers for progenitor cells of salivary glands, we examined the expression and localization of nestin in damaged tissues by du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Nestin is an intermediate filament protein expressed in the central nervous system stem and progenitor cells 25) , but its expression has also been reported in non-neural stem cells [26][27][28] . The pancreas, liver, and salivary glands are endoderm-derived similar glandular tissues, and these tissues have been reported to have similar structures, functions, and molecular markers 29,30) . Therefore, the regenerative process in the pancreas and liver is very similar to that of salivary glands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nestin is an intermediate filament protein expressed in the central nervous system stem and progenitor cells 25) , but its expression has also been reported in non-neural stem cells [26][27][28] . The pancreas, liver, and salivary glands are endoderm-derived similar glandular tissues, and these tissues have been reported to have similar structures, functions, and molecular markers 29,30) . Therefore, the regenerative process in the pancreas and liver is very similar to that of salivary glands.…”
Section: Discussionmentioning
confidence: 99%
“…Nestin is also a marker of pluripotent stem cells in the central nervous system. Yokoyama et al 29) reported an increase in nestin expression in atrophic acinar cells during the recovery process following unilateral parotid ligation and suggested that it might be a useful marker of salivary gland progenitor cells. However, in this study, there was no significant increase in nestin mRNA levels, and immunostaining revealed nestin-positive reactions in endothelial cells of blood vessels and nerve fibers but not in cells constituting acini or ducts.…”
Section: Discussionmentioning
confidence: 99%
“…Salivary glands recover when the ligation is released 7 days after the duct ligation [19,20]. We previously reported that parotid gland morphology showed weak atrophy of acinar cells in some samples on day 3 of duct ligation, whereas most acinar cells in the parotid gland were atrophied on day 7 of duct ligation [18]. Therefore, the period of duct ligation was set at 7 days for the present study.…”
Section: Ductmentioning
confidence: 97%
“…Mice were injected intraperitoneally with a mixture of medetomidine hydrochloride (0.3 mg/kg), midazolam (4 mg/kg), and butorphanol tartrate (5 mg/kg). Under anesthesia, the unilateral parotid excretory duct was ligated, according to a previously reported procedure [18]. Salivary glands recover when the ligation is released 7 days after the duct ligation [19,20].…”
Section: Ductmentioning
confidence: 99%
“…KEGG pathways that were identified from combination analysis of the 7 down-regulated miRNAs and mRNA expression microarray expression of nestin and cytokeratin-14, stem/progenitor markers, increased during the culture of parotid acinar cells (4,6). In addition, ligation of parotid excretory duct induced expression of nestin and cytokeratin-5 (21,22). After injury, various epithelial cells begin to express nestin, which may indicate a reversion to an immature phenotype.…”
Section: Change In the Expression Level Of Rno-mir-3473 In Parotid Acmentioning
confidence: 99%